2016
DOI: 10.1186/s13550-016-0173-z
|View full text |Cite
|
Sign up to set email alerts
|

Automated Bone Scan Index as a quantitative imaging biomarker in metastatic castration-resistant prostate cancer patients being treated with enzalutamide

Abstract: BackgroundHaving performed analytical validation studies, we are now assessing the clinical utility of the upgraded automated Bone Scan Index (BSI) in metastatic castration-resistant prostate cancer (mCRPC). In the present study, we retrospectively evaluated the discriminatory strength of the automated BSI in predicting overall survival (OS) in mCRPC patients being treated with enzalutamide.MethodsRetrospectively, we included patients who received enzalutamide as a clinically approved therapy for mCRPC and had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
48
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 19 publications
1
48
0
Order By: Relevance
“…The computer‐aided diagnosis system shows the BSI, which provides a quantitative measure of the percentage of the adult skeleton involved in bone metastases . BSI on bone scintigraphy was a predictor of overall survival . Measurement of BSI showed that PSA is not always correlated with the level of bone metastasis .…”
Section: Evaluation Of Imagementioning
confidence: 99%
See 1 more Smart Citation
“…The computer‐aided diagnosis system shows the BSI, which provides a quantitative measure of the percentage of the adult skeleton involved in bone metastases . BSI on bone scintigraphy was a predictor of overall survival . Measurement of BSI showed that PSA is not always correlated with the level of bone metastasis .…”
Section: Evaluation Of Imagementioning
confidence: 99%
“…57,66 BSI on bone scintigraphy was a predictor of overall survival. [67][68][69] Measurement of BSI showed that PSA is not always correlated with the level of bone metastasis. 29 The Prostate Cancer Clinical Trials Working Group 3 also recommends computed tomography to evaluate lymph node metastases and visceral metastases.…”
Section: Androgenindependent Cellsmentioning
confidence: 99%
“…However, as the range of each score is broad, the detailed assessments are limited. In the case of BSI, the amount (%) of bone metastasis can be calculated by adapting the artificial neural network, which enables the detection of precise baseline metastasis, as well as the range of change among metastatic lesions …”
mentioning
confidence: 99%
“…Anand et al . reported the change in BSI was useful in predicting survival in castration‐resistant prostate cancer patients treated with enzalutamide …”
mentioning
confidence: 99%
See 1 more Smart Citation